Pengaruh Gaya Kepemimpinan Kepala Sekolah terhadap Kinerja Guru - Bustanul Arifin Noer; Siti Nurhayati (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2006)
This research aims to test influence of principals' leadership styles toward teachers' achievement at junior secondary school setting. Subjects of the research were 185 teachers from Surabaya city, e.g. Kenjeran region and Bulak region. The research found that principals' leadership styles with 4 construct/latent variables influence teachers' achievement at junior secondary school.